Intermittent enteral nutrition shortens the time to achieve nutritional goals in critically ill patients - Ondrej Hrdy; Kamil Vrbica; Jaroslav Duba; Martin Slezak; Eva Strazevska; Viktor Agalarev; Milos Duba; Radka Stepanova; Adam Svobodnik; Roman Gal (Scientific Reports)
Abstract Nutritional support is associated with improved clinical outcomes in critically ill patients; however, loss of muscle mass during critical illness leads to weakness, delayed return to work, and increased healthcare consumption. Animal data have suggested that intermittent feeding decreases protein catabolism. This study was aimed at determining whether the mode of enteral nutrition administration might lead to differences in meeting nutritional goals, tolerance, and complications. A prospective, randomized, single-center clinical trial was conducted in four intensive care units in the Czech Republic. Critically ill adult patients with high nutritional risk were randomized to continuous or intermittent enteral nutrition administration through a tolerance-driven protocol. The primary outcome was the time to reach the energetic target. Secondary outcomes included assessment of tolerance (high gastric residual volume, vomitus, and diarrhea), complications (aspiration or ventilator-associated pneumonia), and 28-day mortality. A total of 300 patients were randomized, and 294 were analyzed: 148 in the continuous arm and 146 in the intermittent arm. Regarding the primary outcome, log-rank test indicated that the intermittent group, compared with continuous group, had a statistically significantly shorter time (p = 0.009) and greater diarrhea occurrence (7 (4.7%) vs. 16 (11%), p = 0.049). No statistically significant differences in ventilator-associated pneumonia incidence (18 (12.2%) vs. 18 (12.3%), p = 0.965), 28-day mortality (46 (31.1%) vs. 40 (27.4%), p = 0.488), and other secondary outcomes were observed between groups. Thus, intermittent enteral nutrition was superior to continuous enteral nutrition in terms of time to reach the energetic target with the tolerance-driven administration protocol but was associated with higher diarrhea incidence. No statistically significant differences in the other secondary outcomes were observed.